Adaptive Reuse of Urban Heritage in Contested Urban Contexts: The Case of Acre in Israel - Yarza Pérez, Ana Jayone (A+BE | Architecture and the Built Environment, 2024)
The world is facing global challenges that are dramatically changing the social and physical environments, resulting in cultural confrontation. Rapid urban growth, and gentrification increase urban pressure while jeopardizing social cohesion, multicultural values and local economies. Moreover, environmental factors associated with climate change challenge the way cities respond and adapt, as their assets have to be re-designed to meet the current and future generation needs. One response to these challenges is adaptive reuse, the transformation of the function of an underused structure into a new use. This process turns the cities’ elements in decline into development catalysers. The adaptation to these changes is often a source of conflict, as urban policies lack citizen engagement in the redefinition of public space, resulting in more disagreement. This is particularly acute when addressing contested communities, as their continuous evolution directly influence the adaptation of cultural heritage. Considering these aspects, this research question is responded: ‘How can socio-spatial conflicts that result from contested identities be mitigated through the adaptive reuse of urban heritage?’. The relations between Adaptive Reuse, Urban Heritage and Contested Identities are studied, resulting in the research’s objective: to develop an integrative methodology to evaluate urban heritage adaptive reuse alternatives in contested urban contexts, using the case of Acre (Israel). This final outcome is proposed as a tool for decision-makers and urban planners that provides information-based results to be applied in urban design practice, aiming to translate the theory into practice, and to bridge the gap between global goals and local issues.